Achievement Emotions in EFL Listening Class: A Quantitative Study Using AEQ-S - Sumanto, Ossa Bodhi Tala; Aini, Alfina Nur; Aulia, Nurul Putri; Syaputri, Nur Ely (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2025)
In English language learning, productive skills such as speaking and writing are often prioritized, while a vital receptive skill such as listening is frequently assumed as a secondary status. This undervaluation contributes to negative stereotypes and adds the challenges faced by EFL learners. Among the overlooked matters is the emotional experience of learners, which provides a crucial role, particularly in skill-based course like listening that demand sustained attention and confidence. This study aims to examine the achievement emotions experienced by EFL learners in listening class using the Achievement Emotions Questionnaire – Short (AEQ-S), developed by Pekrun et al. (2011). A total of 37 university students completed the AEQ-S, which measures both positive and negative emotions across three domains: classroom activities, learning processes, and test-taking situations. The data were analyzed using descriptive statistics and paired-sample t-tests. The finding revealed a significant difference in all three contexts. In classroom-related activities, positive emotions (M = 3.78, SD = 0.65) were significantly higher than negative emotions (M = 2.50, SD = 0.71), (t(36) = 6.947, p < .001). A similar trend was found in learning-related (t(36) = 6.139, p < .001) and test-related situations (t(36) = 5.488, p < .001), indicating the consistency of emotional dominance across academic conditions with enjoyment as the most frequently experienced emotion. These findings highlight the critical need to integrate emotional consideration into listening pedagogy. By fostering emotionally supportive environments, educators can enhance learners' engagement and aid them to navigate the challenges of listening comprehension.